Vitamin D Deficiency and Its Association with Thyroid Disease - Mackawy, Amal Mohammed; Al-ayed, Bushra Mohammed; Al-rashidi, Bashayer Mater (International Journal of Health Sciences, 2013)
<!–[if gte mso 9]> <![endif]–><p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">Objectives: Vitamin D deficiency is a global health problem, its role as an immune modulator has been recently emphasized. The evidence is increasingly pointing towards vitamin D significant role in reducing the incidence of autoimmune diseases. However, at this time the research on its role in autoimmune and thyroid disease is not conclusive. <p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">Â <p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">We aimed to examine the relationship between hypothyroidism and vitamin D deficiency and to clarify the relation between serum calcium levels with hypothyroid disease. <p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">Â <p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">Subjects and Methods: Serum vitamin D (25-OH) levels were measured in 30 patients with hypothyroidism and 30 healthy subjects, utilizing the spectrophotometric method. Vitamin D deficiency was designated at levels lower than 20Â ng/ml. Thyroid hormones (TSH, T3 and T4) and calcium levels were evaluated in all participants. <p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">Â <p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">Results: Serum 25(OH) vit D was significantly lower in hypothyroid patients than in controls (t=-11.128, P =0.000). Its level was insignificantly decreased in females than male patients (t=- 1.32, P >0.05). Moreover, serum calcium levels recorded a significant decrease in hypothyroid patients when compared to controls (t= -5.69, P = 0.000). <p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">Â <p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">Conclusion: Our results indicated that patients with hypothyroidism suffered from hypovitaminosis D with hypocalcaemia that is significantly associated with the degree and severity of the hypothyroidism. That encourages the advisability of vit D supplementation and recommends the screening for Vitamin D deficiency and serum calcium levels for all hypothyroid patients. <p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">Â <p class="MsoNormal" style="margin: 0in; margin-bottom: .0001pt; text-align: justify; text-indent: 0in; line-height: normal; tab-stops: right 6.5in; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">Keywords: Vit D deficiency, Blood calcium levels, Thyroid diseases. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>